2022
DOI: 10.1021/acs.jctc.1c00911
|View full text |Cite
|
Sign up to set email alerts
|

py-MCMD: Python Software for Performing Hybrid Monte Carlo/Molecular Dynamics Simulations with GOMC and NAMD

Abstract: py-MCMD, an open-source Python software, provides a robust workflow layer that manages communication of relevant system information between the simulation engines NAMD and GOMC and generates coherent thermodynamic properties and trajectories for analysis. To validate the workflow and highlight its capabilities, hybrid Monte Carlo/molecular dynamics (MC/MD) simulations are performed for SPC/E water in the isobaric–isothermal (NPT) and grand canonical (GC) ensembles as well as with Gibbs ensemble Monte Carlo (GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…As highlighted in some of the examples that follow, it can be computationally advantageous to utilize NAMD to quickly equilibrate the system using MD and then perform the desired MC simulations using GOMC. MoSDeF-GOMC can also build PDB, PSF, and parameter files for py-MCMD, another Python software that utilizes both NAMD and GOMC to perform hybrid MD/MC simulations. However, unlike standard GOMC simulations, py-MCMD requires custom GOMC and NAMD control files that the user must modify outside of the MoSDeF-GOMC framework.…”
Section: Software Architecturementioning
confidence: 99%
“…As highlighted in some of the examples that follow, it can be computationally advantageous to utilize NAMD to quickly equilibrate the system using MD and then perform the desired MC simulations using GOMC. MoSDeF-GOMC can also build PDB, PSF, and parameter files for py-MCMD, another Python software that utilizes both NAMD and GOMC to perform hybrid MD/MC simulations. However, unlike standard GOMC simulations, py-MCMD requires custom GOMC and NAMD control files that the user must modify outside of the MoSDeF-GOMC framework.…”
Section: Software Architecturementioning
confidence: 99%
“…With the development of computer technology and simulation software, simulation technology has been shown to greatly reduce the cost of material development and improve work efficiency [ 21 , 22 , 23 , 24 , 25 , 26 ]. A molecular dynamic simulation optimization experiment showed that an efficiency ratio of running time that tended to balance judgment achieved the highest value of 36.96% [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact determination of the FES for large proteins is challenging, as it requires extensive sampling of the protein's conformational space. New methods for computational protein structure prediction [15][16][17] and simulation [18][19][20][21][22] are emerging and there is an increased availability protein structure datasets. However, a full understanding of a protein's dynamics can be reached only when the dataset spans the FES sufficiently, allowing quantitative methods (such as Markov state modeling) to be applied.…”
Section: Introductionmentioning
confidence: 99%
“…Many computational packages have since been developed, including NAMD [33], GROMACS [34,35], AMBER [36], CHARMM [37], OpenMM [38]. MD software is becoming more accessible with python plugins and graphical user interfaces [18]. Markov State Modelling (MSM) approaches for interpreting MD simulations [39] have recently gained popularity.…”
Section: Introductionmentioning
confidence: 99%